Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø¨ÙŠÙ† Ø§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù‚Ø±Ø¢Ù† Ùˆ Ù‡Ù…Ø© Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„ØµÙ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨ØªØ±Ø¨ÙŠØ© ØªØ¹Ø§Ø¯Ù„ Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø³Ù„ÙÙŠØ© Ù‡Ø¯Ø§ÙŠØ© Ø§Ù„Ù‚Ù…Ø±ÙŠØ© Ø¨Ù†Ø¬ÙƒÙˆÙ„Ùˆ - Windi Andriani (UIN Fatmawati Sukarno Bengkulu, 2023)
This research is a quantitative type of correlational research. This study aims to determine the relationship between the ability to read the Al Qurâ€™an with an interest in learning Arabic in grade 8 female students of the Equalization Education of Salafiyah Hidayatul Qomariyah Islamic Boarding School Bengkulu. The entire data obtained was analyzed using descriptive statistical analysis and parametric inferential statistical analysis with the Pearson Product Moment bivariate correlation type. The results showed that the calculation of the relationship between the ability to read the Koran and the interest in learning Arabic in grade 8 female students of the Equalization Education of the Salafiyah Hidayatul Qomariyah Islamic Boarding School Bengkulu had a correlation value (r count) of 0.125 with a very weak interpretation value. Based on the results of this study, it is suggested to Arabic teachers to make methods and media more interesting and intensively motivating female students about the importance of learning Arabic so that there is a high interest in learning Arabic.Â Keywords: ability to read the Al Qurâ€™an, interest in learning Arabic, Hidayatul QomariyahÂ